Make me proud! Singapore 2010 Youth Olympic Games and its effect on national pride of young Singaporeans. (December 2014) - Leng, Ho Keat; Kuo, Tzu-Yin; Baysa-Pee, Grain; Tay, Josephine
Politicians and sports organizations have often relied on economic benefits to justify their decisions in hosting major sports events in their countries. Consequently, there are comparatively few studies on the non-economic benefits of hosting major sports events. The purpose of this research is to determine whether there is any change in the level of national pride in the hosting of the Youth Olympics Games held recently in Singapore in 2010. Two separate surveys were conducted among students from a tertiary education institution in Singapore two months prior to, and after, the event. Results showed a significant increase in the level of national pride. Specifically, the increases in the level of national pride were more pronounced among males and those who were more involved in sports. The results concur with previous studies that have reported an increase in national pride following the hosting of a major sports event. As this is a case study focusing on the Youth Olympic Games, which arguably is on a distinctly smaller scale compared to the Olympics or the FIFA World Cup, future research needs to be conducted on other major sports events to determine the generalizability of the findings.